Assessment of Passenger Safety Perception in Informal Public Transportation in Lokoja-Okene Road Transport Network, Kogi State, Nigeria - Ohida, Muhammed Etudaiye; Ajiboye, Araoye Olarinkoye; Gana, Moses Danjuma; Yakubu, Talatu Rukayat; Oluwabunmi, Simeon Aderonke (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2025)
Informal public transport, as a mode of transportation, offers flexibility to users by allowing them to access services conveniently. However, its mode of operation poses significant challenges, particularly regarding safety, thereby undermining the core objective of ensuring safe travel. This study employs a survey research design to investigate passengers' safety perceptions in informal public transport along the Lokoja-Okene transport corridor. A total of 300 questionnaires were purposefully distributed among commuters using the Lokoja-Okene transport network, with 255 valid responses analyzed using frequencies and percentages. The relationship between passenger safety and factors influencing it was analysed using multiple regression analysis. The findings identified eight key factors affecting passenger safety, including vehicle condition (37.5%), driver driving behavior (41.9%), poor road conditions (57.7%), overloading (42.6%), and driver operational behaviour (46%). Furthermore, a statistically significant relationship was established between passenger safety and factors such as driver behavior, operational practices, and vehicle condition, which were found to influence passengers' safety perceptions positively. In conclusion, informal public transport operations along the Lokoja-Okene road network are deemed highly unsafe. The study recommends, among other measures, that Kogi State Vehicle Inspection Officers (VIOs) implement mandatory periodic inspections for vehicles operating in informal public transport along this route.